National governance of de-implementation of low-value care: a qualitative study in Sweden - Hanna Augustsson; Belén Casales Morici; Henna Hasson; Ulrica von Thiele Schwarz; Sara Korlén Schalling; Sara Ingvarsson; Hanna Wijk; Marta Roczniewska; Per Nilsen (BMC, 2022)
Abstract Background The de-implementation of low-value care (LVC) is important to improving patient and population health, minimizing patient harm and reducing resource waste. However, there is limited knowledge about how the de-implementation of LVC is governed and what challenges might be involved. In this study, we aimed to (1) identify key stakeholders' activities in relation to de-implementing LVC in Sweden at the national governance level and (2) identify challenges involved in the national governance of the de-implementation of LVC. Methods We used a purposeful sampling strategy to identify stakeholders in Sweden having a potential role in governing the de-implementation of LVC at a national level. Twelve informants from nine stakeholder agencies/organizations were recruited using snowball sampling. Semi-structured interviews were conducted, transcribed and analysed using inductive thematic analysis. Results Four potential activities for governing the de-implementation of LVC at a national level were identified: recommendations, health technology assessment, control over pharmaceutical products and a national system for knowledge management. Challenges involved included various vested interests that result in the maintenance of LVC and a low overall priority of working with the de-implementation of LVC compared with the implementation of new evidence. Ambiguous evidence made it difficult to clearly determine whether a practice was LVC. Unclear roles, where none of the stakeholders perceived that they had a formal mandate to govern the de-implementation of LVC, further contributed to the challenges involved in governing that de-implementation. Conclusions Various activities were performed to govern the de-implementation of LVC at a national level in Sweden; however, these were limited and had a lower priority relative to the implementation of new methods. Challenges involved relate to unfavourable change incentives, ambiguous evidence, and unclear roles to govern the de-implementation of LVC. Addressing these challenges could make the national-level governance of de-implementation more systematic and thereby help create favourable conditions for reducing LVC in healthcare.